Aspek Petrografi Batugamping di Daerah Timor Tengah Selatan - Sigit Maryanto; Asep Kurnia Permana; Joko Wahyudiono (Jurnal Geologi dan Sumberdaya Mineral, 2018)
Microfacies and diagenetic aspects of limestones in the South Central Timor, East Nusa Tenggara have studied to investigate the deposition mechanism of the rocks and history of geological process after the rocks deposition. The cropped out of limestones in the research area includes into four rock units, are Aitutu Formation from Triassic, Nakfunu Formation from Early Cretaceous, Menu Formation from Late Cretaceous, and Ofu Formation from Paleogene. Limestone petrography analysis have been done on eighteen samples from the Aitutu Formation, fourty two samples from the Nakfunu Formation, nineteen samples from the Menu Formation, and seven samples from the Ofu Formation. Based on the study of limestones mikrofasies and diagenesis that has been done, proved are the fourth formation could be act as a source and reservoir for hydrocarbon.Â Keywords: Limestone, petrography, microfacies, diagenetic, hydrocarbon